Sixteen-Year Follow-up of Talar Body Prosthesis and Total Ankle Arthroplasty After Traumatic Talar Extrusion: A Case Report. Issue 1 (January 2021) - Benson, Austin; Alvine, Frank; Alvine, Greg
Abstract : Case: We report a case of an extruded talus treated with an agility custom talar body prosthesis with total ankle arthroplasty 2 years after the injury. At the 16-year follow-up, the patient has performed remarkably well. At postoperative year 15, she required 1 additional surgery in which the polyethene was exchanged and the medial and lateral gutters were debrided. Conclusion: Talar body prothesis with total ankle arthroplasty may be a viable option for extrusion of the talus.